Green Products in Banks. Case of an Emerging Country - JABER, Yasmina; SALEM, Faten Nasfi (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special IssueDO - 10.14505/tpref.v15.2(30).19, 2024)
This paper explored in depth the issue of green finance within Tunisian banks. The main objective of this research was to understand how Banks can play a significant role in the development of green finance in Tunisia. In a first step, we explained the undeniable importance of green finance which presents an essential pillar of the transition towards a more sustainable and environmentally friendly economy. Financial institutions play a vital role in promoting green financial products. Banks have started to offer products and services focused on sustainability. However, these efforts are insufficient, and it is necessary to strengthen them. For this, we examined the perception of Tunisian customers towards the green financial products of Banks as well as the factors influencing their attitudes, a detailed survey reveals that awareness is growing and that trust and relevance are crucial elements to encourage their adoption. In conclusion, this work has highlighted the importance of green finance in the Tunisian context. It offers food for thought for decision-makers, practitioners, and researchers who wish to contribute to the sustainable development of the banking sector in Tunisia.